A Framework to Support Experiential Learning and Psychological Flexibility in Supervision: SHAPE. (April 2017) - Morris, Eric M.J.; Bilich‐Eric, Linda
Abstract : Objective: In this article, we describe a pragmatic framework for supporting supervision, based on a contextual behavioural perspective. Method: The development of psychological skills to a competent level requires didactic and experiential learning, and supervision is agreed to be a central vehicle for the integration of these experiences. Alongside engaging in problem‐solving and giving instructions (to build adherence), supervisors can reasonably expect supervisees to learn from experience by attending closely to influences and effects of their choices . Experiential learning can help the psychologist to develop sensitivity in applying knowledge and skills in effective and safe ways for clients (thus demonstrating competence). Results: We argue that contingency‐shaped learning is strengthened by including supervision elements that promote psychological flexibility (the capacity to actively embrace one's private experiences in the present moment and engage or disengage in patterns of behaviour in the service of chosen values). Psychological flexibility has been found to foster wellbeing, work effectiveness, openness to new learning, compassion, and acceptance of difference and diversity, in workplace settings. Moreover, the psychological flexibility of psychologists has been found to predict the use of evidence‐based interventions, such as exposure. Conclusion: The SHAPE framework identifies five features (Supervision values; Hold stories lightly; Assessment of function; Perspective‐taking; Experiential methods) likely to promote psychologists' psychological flexibility and experiential learning in the supervision context. These five features are extensions of agreed supervision best practices, enhanced by developments in contextual behavioural science (perspective‐taking, cognitive defusion, and acceptance). We describe examples of using SHAPE, and present research directions, to assess whether these features promote experiential learning in supervision.